Simultaneous Determination of Organic Acids in Chinese Liquor by GC-MS Method - Ma, Yanhong; Li, Meiping; Zhang, Shengwan (Asian Journal of Chemistry, 2014)
A reliable method for determining the organic acids in Chinese liquors by derivatization GC-MS is reported. Acetic acid, butyric acid, isovaleric acid, pentanoic acid, caproic acid, heptylic acid and lactic acid were quantified in this text. The SIM mode was employed in the analysis and presented high accuracy, reproducibility and reduced the matrix effect effectively. The calibration curves were obtained with a satisfactory correlation coefficient of 0.9929 to 0.9994. The precision results showed that the relative standard deviations (RSD) of the repeatability were < 3.01 %. The accuracy of the method was confirmed with an average recovery ranging between 82.43 % and 109.38 %. The proposed method was used for the determination of organic acids in Chinese liquor. Application to different kinds and ages of Chinese liquor confirmed good repeatability and wide variation range for organic acids.